A modular cement-based subsurface heat storage: Performance test, model development and thermal impacts. (1st December 2020) - Nordbeck, Johannes; Bauer, Sebastian; Dahmke, Andreas; Delfs, Jens-Olaf; Gomes, Hugo; Hailemariam, Henok; Kinias, Constantin; Meier zu Beerentrup, Kerstin; Nagel, Thomas; Smirr, Christian; Vienken, Thomas; Wuttke, Frank; et al.
Highlights: A modular cement based heat storage system is evaluated by experiments and modeling. A field scale storage pilot plant is constructed in the shallow subsurface. A geometrical simplification approach substantially reduces the numerical grid size. Experimental and modeling results demonstrate the systems technical feasibility. The model approach is useful also for energy pile or borehole heat exchanger models. Abstract: This study investigates the performance of a recently developed modular cement based underground thermal energy storage concept and its thermal impacts on the geological subsurface by experimental work and numerical modeling. A field-scale pilot plant of the storage system was constructed in the shallow subsurface in northern Germany, consisting of 25 coupled 1.5 m 3 storage units containing a tubular helical heat exchanger. A charging and passive cooling experiment was performed and monitored over a period of 82 days. For the numerical model of the storage and the surrounding ground a geometrical grid simplification procedure was developed, which substantially reduces the computational effort for 3D-simulations of multi-unit storage arrays. The model was validated by comparison of experimental and simulation data and used to corroborate the interpretation of the field test. Results show heat transfer rates of 15.2–2.8 kW during the first ten days, storing about 1280 kWh of thermal energy. During passive cooling the average heat loss rate amounts to 28 kWh/day. The results demonstrate the technical feasibility of the storage concept at low thermal impact on the subsurface environment but also the necessity for an improved insulation in order to increase the storage efficiency. The numerical modelling approach can be applied for layout and operational optimization as well as thermal impact assessment for specific applications of the modular storage system, but is useful also for grid size reduction in models of related geothermal subsurface structures employing tubular heat exchangers like thermally activated pile foundations or borehole heat exchangers.